2017
DOI: 10.1101/132696
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A high resolution atlas of gene expression in the domestic sheep (Ovis aries)

Abstract: Sheep are a key source of meat, milk and fibre for the global livestock sector, and an important biomedical model. Global analysis of gene expression across multiple tissues has aided genome annotation and supported functional annotation of mammalian genes. We present a large-scale RNA-Seq dataset representing all the major organ systems from adult sheep and from several juvenile, neonatal and prenatal developmental time points. The Ovis aries reference genome (Oar v3.1) includes 27,504 genes (20,921 protein c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 134 publications
(82 reference statements)
1
13
0
Order By: Relevance
“…In turn, this may facilitate the identification of novel therapeutic targets for both endotoxaemia and sepsis in man, an objective which has been met with limited success via the use of rodent models. Similar studies have already been performed in other large animal models such as pig and sheep 60,61,211 …”
Section: The Horse As An Animal Model For Human Disease Researchsupporting
confidence: 72%
See 2 more Smart Citations
“…In turn, this may facilitate the identification of novel therapeutic targets for both endotoxaemia and sepsis in man, an objective which has been met with limited success via the use of rodent models. Similar studies have already been performed in other large animal models such as pig and sheep 60,61,211 …”
Section: The Horse As An Animal Model For Human Disease Researchsupporting
confidence: 72%
“…In mice, macrophages are routinely generated in vitro from bone marrow progenitors for subsequent functional studies 58,59 . This approach has recently been extended to large animal species expedited by the capacity to freeze cells for future culture following recovery 21,60‐62 . We have recently published a comparative analysis of RNA‐seq data of horse BMDM and their response to lipopolysaccharide (LPS) with similar data for ruminants (sheep, goat, cow and water buffalo), pig, mouse and rat (in press).…”
Section: The Mononuclear Phagocyte System Of the Horsementioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this view, analysis of the pig gene expression atlas (Freeman et al 2012) revealed that there were a large number of genes for C-type lectins that were highly-expressed in alveolar macrophages but almost undetectable in the pig GI tract despite the high expression of known macrophage-specific transcripts (Freeman et al 2012). To determine if this was also the case in sheep we examined the expression of six C-type lectin marker genes ( CD68 , CLEC4D , CLEC4E , CLEC5A , CLEC7A and SIGLEC1 ) using the gene expression profiles for the sheep atlas dataset on BioGPS (Clark et al 2017a). In sheep, as in pig, CLEC4D , CD68 , CLEC4E and CLEC7A were all highly expressed in sheep alveolar macrophages, but barely detected in the GI tract tissues.…”
Section: Resultsmentioning
confidence: 99%
“…In mice, macrophage-specific conditional deletion of the IL10 receptor causes severe spontaneous colitis (Zigmond et al 2014) as does a full mutation of the IL10 gene (Kühn et al 1993). In the sheep atlas dataset on BioGPS, IL10 mRNA is strongly induced in macrophages by lipopolysaccharide (Clark et al 2017a). However, the induction is rapid and transient, and decays completely after 24 hr.…”
Section: Resultsmentioning
confidence: 99%